2017
DOI: 10.1016/j.tca.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior, spectroscopic studies and free radical scavenging potential of some mefenamate trivalent lanthanides (Sm, Eu, Gd, Tb and Dy)

Abstract: a b s t r a c tLanthanide Mefenamate compounds were prepared in solid state. TG-DSC coupled to FTIR, elemental analysis, complexometry with EDTA, X-ray powder diffractometry, evaluation of scavenging free radical activity with DPPH (2,2-diphenyl-1-picryl-hydrazine), and a complete spectroscopic study in the ultraviolet, visible, near-, and middle-infrared regions were realized to obtain some physicochemical properties of the synthesized compounds. The thermal stability, minimum formula, thermal behavior and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…As one can see, the Δν values for the complexes are slightly lower but close to the sodium salt, indicating that the fluf ligand coordinates to Ln 3+ ions through a bidentate chelate coordination mode . These results are corroborated with the FTIR data reported in previous reports. ,, The coordination of ancillary ligands to the Ln 3+ ion was confirmed by the shift of the heteroaromatic C–N mode and the phosphine oxides (ν PO ) and sulfoxide (ν SO ) stretching modes to lower energies when compared with the free organic molecules, as can be seen in Table S2.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…As one can see, the Δν values for the complexes are slightly lower but close to the sodium salt, indicating that the fluf ligand coordinates to Ln 3+ ions through a bidentate chelate coordination mode . These results are corroborated with the FTIR data reported in previous reports. ,, The coordination of ancillary ligands to the Ln 3+ ion was confirmed by the shift of the heteroaromatic C–N mode and the phosphine oxides (ν PO ) and sulfoxide (ν SO ) stretching modes to lower energies when compared with the free organic molecules, as can be seen in Table S2.…”
Section: Resultssupporting
confidence: 86%
“…34 These results are corroborated with the FTIR data reported in previous reports. 27,33,35 The coordination of ancillary ligands to the Ln 3+ ion was confirmed by the shift of the heteroaromatic C−N mode and the phosphine oxides (ν P�O ) and sulfoxide (ν S�O ) stretching modes to lower energies when compared with the free organic molecules, 36−38 as can be seen in Table S2.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Complexes with molecules used as medications have been extensively studied due to their biological and spectroscopic properties. Recent studies on lanthanide complexes with nonsteroidal drugs, such as mefenamic acid, ketoprofen, and oxyphenbutazone, found that they exhibit unique spectroscopic and biological properties with applications in biological and technological fields [17][18][19][20]. Complexes with enrofloxacin, ciprofloxacin, norfloxacin, Electronic supplementary material The online version of this article (https://doi.org/10.1007/s10973-018-7042-0) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%